THE DISCOURSE OF SUICIDE: BETWEEN MYTH AND REALITY - Suwena, I Wayan (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
People thinking mythically are oriented towards myths in response to particular incidents like responding to suicide incident in Gunungkidul. The suicide incident in this region is legitimized by the pulung gantung myth. However, for realistically minded people they do not believe that people commit suicide due to downfall or getting possessed by pulung gantung. Thus, this paper aims to understand and analyze the discourse of mythically and realistically minded people in the context of suicide incidents. When a suicide occurs, the mystically minded people will attribute this incident to the myth of pulung gantung. They believe that prior to a suicide incident is often marked with the appearance of pulung gantung. The pulung gantung resembles to a fireball. When this appears, it is interpreted that it looks for a mind-empty person. The person who is experiencing the empty-mindedness will easily experience a downfall or get possessed by the fireball to commit suicide. In contrast to the discourse of the realistically minded people, the fireball is just a natural phenomenon. They discourse that people committing suicide in this region happens because they are experiencing unresolved problems in life. The suicide issues are usually not single. This situation causes the people concerned to experience depression. When they are depressed and nobody is involved in their communication, ultimately they are desperate and vulnerable to commit suicide.